Electrode tab, secondary battery, and electric device

CN122991979APending Publication Date: 2026-10-27XIAMEN AMPACE TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611160937.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]这种分布带来两个问题:一是涂层中间致密层阻碍离子迁移,扩散阻抗偏高;二是极片中央区域虽孔隙率略高,但处于电芯热中心与电流中心,离子传输仍滞后于电子传输,易达到析锂电位,长期循环后形成“中圈黑斑”,影响寿命与安全

Benefits of technology

[0024]上述说明仅是本申请技术方案的概述,为了能够更清楚了解本申请的技术手段,而可依照说明书的内容予以实施,并且为了让本申请的上述和其它目的、特征和优点能够更明显易懂,以下特举本申请的具体实施方式。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122991979A_ABST
    Figure CN122991979A_ABST
Patent Text Reader

Abstract

The application discloses an electrode tab, a secondary battery and an electric device. The electrode tab comprises a current collector and an active material layer. The active material layer is arranged on at least one side of the current collector. The active material layer comprises a first region, a first middle region and a second region arranged in sequence along the thickness direction. Along the direction from the first region to the first middle region, the porosity of the active material layer decreases; along the direction from the first middle region to the second region, the porosity of the active material layer increases, and the increasing change amount is less than or equal to the decreasing change amount. The technical scheme of the embodiment of the application adjusts the pore structure distribution of the electrode tab, improves the ion movement speed, and thus enables the electrode tab to improve the rapid charging and discharging capacity while ensuring the energy density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of batteries, and in particular to an electrode sheet, a secondary battery, and an electrical device. Background Technology

[0002] Secondary batteries are widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric cars, electric airplanes, electric ships, power tools, and energy storage devices.

[0003] In conventional electrode fabrication processes, the active material coating will naturally form an uncontrollable porosity distribution due to the drying and rolling processes: dense in the middle and loose on both sides in the thickness direction; dense at the edges and loose in the center in the width direction.

[0004] This distribution leads to two problems: First, the dense layer in the middle of the coating hinders ion migration and has a high diffusion resistance; second, although the porosity in the central region of the electrode is slightly higher, it is located at the thermal and current center of the cell, so ion transport still lags behind electron transport, making it easy to reach the lithium plating potential. After long-term cycling, "middle-ring black spots" are formed, affecting lifespan and safety. Summary of the Invention

[0005] In view of the above problems, this application provides an electrode sheet, a secondary battery, and an electrical device. By adjusting the pore structure distribution of the electrode sheet, the ion movement speed is increased, thereby enabling the electrode sheet to improve its rapid charge and discharge capability while ensuring energy density.

[0006] In a first aspect, this application provides an electrode sheet, including a current collector and an active material layer. The active material layer is disposed on at least one side of the surface of the current collector, and includes a first region, a first central region, and a second region sequentially disposed along the thickness direction. The thickness of the active material layer is H. The first region is a region extending 0.1H thickness away from the surface of the current collector in a direction away from the current collector. The second region is a region extending 0.1H thickness away from the surface of the current collector in a direction towards the surface of the current collector. The first central region is a region located 0.4H to 0.6H from the surface of the current collector in the thickness direction. Along the direction from the first region to the first central region, the porosity of the active material layer decreases; along the direction from the first central region to the second region, the porosity of the active material layer increases, and the increase is less than or equal to the decrease.

[0007] In the technical solution of this application embodiment, the high-porosity regions on both sides near the current collector and the separator construct efficient ion channels, reducing wetting resistance and interfacial impedance, and alleviating concentration polarization at high rates. The low-porosity region in the middle serves as a dense framework, providing mechanical support while ensuring high volumetric energy density, buffering charge-discharge volume expansion, and preventing electrode cracking. The increase in porosity on the separator side is less than the decrease on the current collector side, strengthening the separator interface where ion exchange is most frequent, further improving fast-charging capability and cycle life, and achieving a balance between high energy density, high-rate performance, and long-cycle stability. Furthermore, setting the porosity on the current collector side to be greater than that on the separator side can balance the contradictions between electrolyte transport, interfacial reaction, and mechanical stability, and better adapt to high-load or high-rate battery systems.

[0008] In some embodiments, the porosity of the active material layer monotonically decreases along the direction from the first region to the first central region, and the rate of decrease gradually decreases; while the porosity of the active material layer monotonically increases along the direction from the first central region to the second region, and the rate of increase gradually increases. The above technical solution, by defining the porosity as a monotonically decreasing trend with a gradually increasing rate of decrease from the first region to the first central region, and a monotonically increasing trend with a gradually decreasing rate of increase from the first central region to the second region, constructs a nonlinear gradient structure with continuous curvature. This smooth transition eliminates the interfacial impedance jump caused by abrupt changes in porosity, making the ion transport resistance change uniform and avoiding a sharp increase in local concentration polarization. Simultaneously, it effectively disperses the volume expansion stress during charging and discharging, reducing the generation of microcracks and the shedding of active material due to stress concentration.

[0009] In some embodiments, the porosity of the first region is ε1, the porosity of the first middle region is ε2, and the porosity of the second region is ε3, wherein ε1, ε2, and ε3 satisfy at least one of the following: 1) ε3 / ε2≤ε1 / ε2; 2) 1.5 ≤ ε1 / ε2 ≤ 3; optionally, 1.5 ≤ ε1 / ε2 ≤ 2.5; 3) 1.5 ≤ ε3 / ε2 ≤ 3; optionally, 1.4 ≤ ε3 / ε2 ≤ 2.25; 4) The porosity ε1 in the first region ranges from 30% to 50%. 5) The porosity ε2 in the first central region ranges from 20% to 25%. 6) The porosity ε3 of the second region is in the range of 35%≤ε3≤45%.

[0010] The above technical solution optimizes electrode performance by limiting the specific ratios and ranges of ε1, ε2, and ε3. ε2 / ε3 ≤ ε2 / ε1 strengthens the ion channels on the separator side, improving fast charging and rate response; the reasonable difference between 1.5 ≤ ε1 / ε2 ≤ 3 and 1.5 ≤ ε3 / ε2 ≤ 3 ensures ion transport on both sides while avoiding structural looseness, balancing rate performance and mechanical strength; ε1 (30%–50%) stores more electrolyte, reducing the interfacial impedance of electrons entering the current collector from the active material, promoting rapid lithium-ion exchange at the interface; ε2 (20%–25%) ensures the mechanical strength and volumetric energy density of the electrode, avoiding energy density loss due to excessive overall porosity; ε3 (35%–45%) stores more electrolyte, reducing lithium-ion concentration polarization at the separator interface, accelerating lithium-ion migration from the electrode to the separator. Ultimately, this achieves a balance between high energy density, high rate capability, and long cycle life.

[0011] In some embodiments, along the thickness direction of the active material layer, with the surface facing the current collector as Z=0, the surface facing away from the current collector as Z=H, and the center of the first central region as Z=H / 2, the porosity ε(Z) at any thickness position Z satisfies the following functional relationship: ε(Z)=ε min +(ε max -ε min )×[(2Z / H-1) 2 ].

[0012] Among them, ε(0) ≤ε(H), ε(H / 2)=ε min , ε max The maximum porosity corresponding to the first and second regions is ε. min This corresponds to the minimum porosity in the first central region.

[0013] The aforementioned technical solution, by introducing the quadratic function relationship, constructs a gradient pore structure with continuous and adjustable curvature. Compared to piecewise linear or discrete gradient designs, the quadratic function eliminates the interfacial impedance jumps and stress concentration points caused by abrupt changes in porosity, allowing for a smooth transition of ion transport resistance in the thickness direction and effectively suppressing local concentration polarization and microcrack formation. Simultaneously, this mathematical model provides precise calculation guidance for setting the porosity of electrode sheets, improving the rate performance and cycle life of the battery while ensuring high volumetric energy density and mechanical stability.

[0014] In some embodiments, the electrode sheet has a first edge and a second edge disposed opposite to each other along its width direction, and the active material layer includes a third region, a second central region, and a fourth region disposed sequentially along its width direction. The third region, the second central region, and the fourth region are spatially overlapping regions formed by the first region, the second region, and the central region intersecting each other in the width direction of the electrode sheet. The second central region is located between the third region and the fourth region, and the porosity of the second central region is greater than that of the third region and the fourth region.

[0015] In the aforementioned structure, the high porosity of the second central region acts as an electrolyte retention structure, absorbing electrolyte, compensating for the ion deficiency in the center of the cell, and suppressing defects such as localized lithium plating and black spots in the central ring. The central ring refers to the circular region defined by the geometric center of each electrode layer and a radius of 10% to 30% of the short side dimension of the electrode, within the plane formed by the width and length directions. Preferably, the radius of the central ring is 15% to 25% of the short side dimension of the electrode. This region is located at the thermal and current center of the cell, with the worst heat dissipation conditions and the highest local current density, making it the primary site for "black spot" failure. This structure actively compensates for the problem of excessively rapid ion consumption in the central ring region due to poor heat dissipation and high local current density, while simultaneously suppressing the low porosity disadvantage naturally formed in the edge regions due to rapid drying rates and concentrated rolling pressure, thereby improving the cell's rate performance, cycle life, and safety.

[0016] In some embodiments, the porosity gradually increases along the direction from the third region toward the second central region, and gradually decreases along the direction from the second central region toward the fourth region.

[0017] The aforementioned structure, with its gradually varying porosity, ensures a uniform distribution of electrolyte permeation resistance within the plane, guiding the ion flow to converge smoothly from both sides towards the center. This balances the current density distribution within the plane and prevents localized overcharging or lithium plating caused by edge effects. Simultaneously, this continuously transitioning structure enhances the bonding force between the electrode edges and the central region, preventing the initiation and propagation of microcracks due to differences in drying shrinkage.

[0018] In some embodiments, the width of the electrode sheet is W; the second central region is a region extending 0.1W to each side from the center line of the electrode sheet, and the third and fourth regions are regions extending 0.4W from each side edge of the electrode sheet towards the center. The porosity of the third region is ε4, the porosity of the fourth region is ε5, and the porosity of the second central region is ε6, wherein ε4, ε5, and ε6 satisfy at least one of the following: 1) 1.5 ≤ ε6 / ε4 ≤ 3; 2) 1.5≤ε6 / ε5≤3; 3) The value range of ε4 in the third region is 15%≤ε4≤25%; 4) The value range of ε5 in the fourth region is 15% ≤ ε5 ≤ 25%; 5) The range of ε6 in the second central region is 35%≤ε6≤50%.

[0019] The aforementioned structure defines the second central region as a 0.2W range in the center and 0.4W on each side, precisely covering the central area and edge stress concentration areas where heat dissipation is worst in the cell. A porosity ratio of 1.5≤ε6 / ε4≤3 and 1.5≤ε6 / ε5≤3 ensures that the porosity in the central region is significantly higher than on the sides, forming a "high-speed channel" for ion transport, effectively compensating for the lack of ions in the center and suppressing local lithium plating. The low porosity of 15%≤ε4 and ε5≤25% on the sides increases the edge compaction density and mechanical strength, preventing powder shedding and cracking during slitting and winding. The high porosity of 35%≤ε6≤50% in the center provides ample electrolyte wetting space and ion diffusion channels, reducing interfacial impedance. These parameter settings, while ensuring the mechanical integrity of the electrode, achieve highly uniform in-plane current density, significantly extending cycle life.

[0020] In some embodiments, along the width direction of the electrode, from the central region to the third or fourth region, the porosity decreases monotonically, either linearly or exponentially. This structure reduces the interfacial impedance jumps and stress concentrations caused by abrupt changes in porosity, resulting in a more uniform distribution of electrolyte permeation resistance. It guides the ion flow to converge smoothly from both sides towards the center, balancing the planar current density and preventing localized overcharging or lithium plating due to edge effects. Simultaneously, the continuous transition enhances the bonding force between the electrode edge and center, preventing microcracks caused by differences in drying shrinkage, and improving the electrochemical uniformity and cycle stability of the secondary battery.

[0021] In some embodiments, the porosity at any point within the active material layer is determined by the coupled gradient distribution in the thickness and width directions. Specifically, the porosity distribution in the thickness direction exhibits a bimodal function characteristic, while the porosity distribution in the width direction shows a monotonically decreasing function characteristic from the center towards the edges. In the above technical solution, the porosity of the electrode sheet in the thickness direction exhibits a gradient characteristic of "high at both sides and low in the middle," forming efficient ion channels on the current collector and separator sides, while the low-porosity region in the middle ensures energy density and structural support. The monotonically decreasing distribution in the width direction from the center towards the edges precisely compensates for the ion deficiency in the central region and enhances the mechanical strength of the edges. Therefore, the above structure achieves spatial uniformity of electrolyte wetting, ion transport, and current density, ensuring high energy density while improving the battery's rate performance, cycle stability, and safety.

[0022] Secondly, this application provides a secondary battery that includes the electrode plates described in the above embodiments.

[0023] Thirdly, this application provides an electrical device that includes the secondary battery described in the above embodiments.

[0024] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description

[0025] The features, advantages, and technical effects of exemplary embodiments of this application will now be described with reference to the accompanying drawings.

[0026] Figure 1 This is a schematic diagram of the structure of a secondary battery according to an embodiment of this application; Figure 2 This is a schematic diagram of the structure of an electrode sheet according to an embodiment of this application; Figure 3 This is a schematic diagram of the structure of an electrode sheet according to an embodiment of this application; Figure 4 This is a schematic diagram of the structure of an electrode sheet according to an embodiment of this application.

[0027] Detailed Explanation of Reference Numerals 1. Secondary battery; 10. Electrode assembly; 101. Tab; 102. Electrode plate; 103. First region; 104. First central region; 105. Second region; 106. Current collector; 107. Active material layer; 108. First edge; 109. Second edge; 110. Third region; 111. Second central region; 112. Fourth region; 20. Housing; 30. Electrode terminal; 31. Terminal assembly; 33. Seal; X, thickness direction; Y, width direction. Detailed Implementation

[0028] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions of the embodiments of this application will be clearly described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of this application, but not all embodiments.

[0029] The terms "first," "second," "third," etc., used in the specification, claims, or accompanying drawings of this application are used to distinguish different objects, not to describe a specific order or hierarchy. In the embodiments of this application, the same reference numerals denote the same components, and for the sake of brevity, detailed descriptions of the same components are omitted in different embodiments.

[0030] In this application, the reference to "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment that is mutually exclusive with other embodiments.

[0031] In the description of this application, it should be noted that, unless otherwise explicitly specified and limited, the terms "installation," "connection," etc., should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.

[0032] In the embodiments of this application, "parallel" includes not only the case of absolute parallelism, but also the case of approximate parallelism as commonly understood in engineering; similarly, "perpendicular" also includes not only the case of absolute perpendicularity, but also the case of approximate perpendicularity as commonly understood in engineering. For example, if the angle between two directions is 80°-90°, the two directions can be considered perpendicular; if the angle between two directions is 0°-10°, the two directions can be considered parallel.

[0033] The secondary battery of this application is described below with reference to the accompanying drawings.

[0034] Reference Figure 1 This application provides a secondary battery 1. The secondary battery 1 can refer to a battery that can be used again after being discharged by recharging to activate the active materials.

[0035] As an example, the secondary battery 1 can be a lithium-ion battery, sodium-ion battery, sodium-lithium-ion battery, lithium metal battery, sodium metal battery, lithium-sulfur battery, magnesium-ion battery, etc.

[0036] As an example, the secondary battery 1 can be a prismatic battery, a pouch battery, or a battery of other shapes. Prismatic batteries include square-shell batteries, blade-shaped batteries, and multi-prismatic batteries, such as hexagonal prismatic batteries.

[0037] The secondary battery 1 includes a housing 20 and an electrode assembly 10 housed within the housing 20.

[0038] Electrode assembly 10 is a component in the secondary battery 1 where an electrochemical reaction occurs. The housing 20 may contain one or more electrode assemblies 10. Exemplarily, the electrode assembly 10 can be a wound structure or a stacked structure.

[0039] The electrode assembly 10 includes electrode plates and a separator. The electrode plates include a positive electrode plate and a negative electrode plate, with opposite polarities. The separator separates the positive and negative electrode plates. During the charging and discharging process of the secondary battery 1, active ions (such as lithium ions) repeatedly insert and extract between the positive and negative electrode plates. The separator, positioned between the positive and negative electrode plates, prevents short circuits between the positive and negative electrodes while allowing active ions to pass through.

[0040] The positive electrode includes a positive current collector and a positive active material layer, the positive active material layer being disposed on the surface of the positive current collector. The negative electrode includes a negative current collector and a negative active material layer, the negative active material layer being disposed on the surface of the negative current collector.

[0041] The positive electrode tab is connected to the positive current collector. In some examples, the positive electrode tab and the positive current collector are a single piece; for example, a layer of positive active material can be coated onto the surface of a metal foil first, and then the positive current collector and the positive electrode tab are formed by die-cutting the metal foil after coating. In other examples, the positive electrode tab and the positive current collector are formed separately and connected separately; for example, the positive electrode tab is welded to the positive current collector.

[0042] The negative electrode tab is connected to the negative electrode current collector. In some examples, the negative electrode tab and the negative electrode current collector are a single piece; for example, a layer of negative electrode active material can be coated onto the surface of a metal foil first, and then the negative electrode current collector and the negative electrode tab can be formed by die-cutting the metal foil after coating. In other examples, the negative electrode tab and the negative electrode current collector are formed separately and connected; for example, the negative electrode tab is welded to the negative electrode current collector.

[0043] Optionally, the positive current collector is aluminum foil, and the negative current collector is copper foil.

[0044] In some embodiments, the secondary battery 1 can be rectangular, square, or other irregularly shaped.

[0045] In some embodiments, the secondary battery 1 includes a terminal assembly 30, which includes electrode terminals 31. One end of the electrode terminal 31 is located inside the housing 20, and the other end is located outside the housing 20. The electrode terminal 31 is connected to a tab (positive tab or negative tab). The electrode terminal 31 is used to connect to an external circuit to enable charging and discharging of the secondary battery 1.

[0046] In some embodiments, electrode terminals 31 are soldered to tabs 101.

[0047] In some embodiments, the terminal assembly 30 further includes a seal 33 surrounding the electrode terminal 31 and disposed between the electrode terminal 31 and the housing 20. The seal 33 can be used to weld with the encapsulation layer of the packaging film 21 to achieve a sealed connection between the terminal assembly 30 and the housing 20.

[0048] In some embodiments, there are multiple terminal assemblies 30, with a portion of the multiple terminal assemblies 30 connected to the positive electrode tab and another portion of the multiple terminal assemblies 30 connected to the negative electrode tab.

[0049] As a core component of lithium-ion batteries, the internal microstructure of the electrode directly determines the battery's electrochemical performance. Conventional electrodes typically consist of a metal current collector and an active material layer coated upon it. The active material layer contains a porous network formed by interwoven active particles, conductive agents, and binders, within which the electrolyte weaves, creating ion transport channels. In conventional manufacturing processes, the porosity distribution of the electrode in both the thickness and width directions often exhibits homogeneity or disorder. This singular or random structure makes it difficult to simultaneously achieve ion transport kinetics and electrode mechanical stability. However, with the ever-increasing demands for energy density and fast-charging performance in batteries, this homogeneous structure has revealed significant technical shortcomings.

[0050] Research has revealed that a uniform pore distribution along the thickness direction cannot match the concentration gradient changes of lithium ions during insertion / extraction, easily leading to concentration polarization in the deeper layers of the electrode or at the interface, resulting in low utilization of active materials. The central region of the electrode, due to poor heat dissipation and slightly greater thickness, is prone to lithium plating due to obstructed ion transport. Therefore, single-dimensional modification methods cannot simultaneously address both the ion transport lag in the thickness direction and the electrochemical inhomogeneity in the width direction, resulting in rapid capacity decay, short cycle life, and significant safety hazards under high-rate charge / discharge conditions.

[0051] To address the aforementioned issues, embodiments of this application provide an electrode sheet with a porosity distribution structure that is high on both sides and low in the middle along the thickness direction of the active material layer. Specifically, higher porosity is provided in the first region near the current collector and the second region near the separator, while lower porosity is provided in the first central region at the center of the electrode sheet. This design precisely matches the transport path requirements of lithium ions during the insertion / extraction process: the high-porosity regions on both sides serve as high-speed channels for rapid ion entry and exit, effectively reducing interfacial impedance and alleviating concentration polarization; the low-porosity central region serves as a high-capacity energy storage reservoir, maximizing volumetric energy density while ensuring structural support.

[0052] like Figure 2 as well as Figure 3As shown, an embodiment of this application provides an electrode sheet 102, including a current collector 106 and an active material layer 107. The active material layer 107 is disposed on at least one side surface of the current collector 106. The active material layer 107 includes a first region 103, a first central region 104, and a second region 105 sequentially disposed along the thickness direction X. The thickness of the active material layer 107 is H. The first region 103 is a region extending from the surface of the current collector 106 in a direction away from the current collector 106 within a thickness range of 0.1H. The second region 105 is a region of the active material layer 107 extending from the surface of the current collector 106 in a direction away from the surface of the current collector 106 within a thickness range of 0.1H. The first central region 104 is a region located in the thickness direction X within a range of 0.4H to 0.6H from the surface of the current collector 106. Along the direction from the first region 103 toward the first central region 104, the porosity of the active material layer 107 shows a decreasing trend; along the direction from the first central region 104 toward the second region 105, the porosity of the active material layer 107 shows an increasing trend, and the amount of increase is less than or equal to the amount of decrease.

[0053] In the technical solution of this application embodiment, the high porosity design on both sides improves the electrolyte wetting speed and ion diffusion coefficient. In particular, the establishment of a fast channel near the current collector 106 solves the problem of low utilization rate of deep active materials and improves the battery's rate charge and discharge performance. The low porosity region in the middle acts as a skeletal support, enhancing the bonding force between the active material layer 107 and the current collector 106, effectively preventing electrode delamination and powder shedding during charge and discharge, and extending cycle life.

[0054] Furthermore, in the actual operation of the secondary battery 1, the process of lithium ions embedding from the electrolyte into the active material layer 107 often faces greater interfacial resistance than the reverse extraction process, which is a key bottleneck limiting fast-charging performance. This application addresses this by limiting the increase in porosity of the second region 105 to be less than the decrease in porosity of the first region 103, and by ensuring that the porosity near the current collector 106 is greater than that near the separator, thus providing a low-impedance channel for ion migration at the electrode root. If the porosity on the current collector 106 side is low, ion transport at the bottom of the electrode will be slower, resulting in low utilization of the active material. This porosity distribution ensures smooth ion transport at the electrode root, reduces concentration polarization, and thereby improves the battery's low-temperature and high-rate performance.

[0055] Furthermore, a dense layer is formed on the surface near the separator, generating a significant capillary attraction. This helps lock the electrolyte inside the electrode, preventing it from leaking out under gravity or vibration, and also facilitates rapid absorption of the electrolyte into the deep layers of the electrode during the initial electrolyte filling process. A loose layer is formed at the bottom near the current collector 106, providing ample electrolyte storage space. This structure creates an upward-absorbing and downward-storing gradient system, significantly improving the electrolyte retention capacity of thick electrodes and preventing battery failure due to internal drying of the electrode (especially near the separator surface) during long-cycle periods. In summary, the asymmetric gradient design of this application optimizes the transport channels while maintaining volumetric energy density. The first region 103, near the current collector 106, has a relatively small decrease in porosity, maintaining a low porosity level and maintaining high compaction density and volumetric energy density as the energy storage framework of the electrode. The high porosity increment is concentrated in the second region 105, precisely serving the ion transport requirements. This spatial functional decoupling achieves both high power density and high energy density without sacrificing overall energy density.

[0056] In some embodiments of this application, the porosity of the active material layer 107 decreases monotonically along the direction from the first region 103 toward the first central region 104, and the rate of decrease gradually decreases; the porosity of the active material layer 107 increases monotonically along the direction from the first central region 104 toward the second region 105, and the rate of increase gradually increases.

[0057] During the transition from the first region 103 to the first middle region 104, the porosity decreases at an accelerated rate; while during the transition from the first middle region 104 to the second region 105, the porosity increases at a decelerated rate. Furthermore, this gradual change forms a smooth curve, eliminating the jump in ion diffusion resistance at the porosity abrupt change interface, avoiding ion accumulation caused by local impedance mismatch, improving the smoothness of ion transport, and thus enhancing the performance stability of the secondary battery 1.

[0058] In some embodiments of this application, the porosity of the first region 103 is ε1, the porosity of the first central region 104 is ε2, and the porosity of the second region 105 is ε3. ε1, ε2, and ε3 satisfy at least one of the following: 1) ε3 / ε2≤ε1 / ε2; 2) 1.5 ≤ ε1 / ε2 ≤ 3; optionally, 1.5 ≤ ε1 / ε2 ≤ 2.5; 3) 1.5 ≤ ε3 / ε2 ≤ 3; optionally, 1.4 ≤ ε3 / ε2 ≤ 2.25; 4) The porosity ε1 of the first region 103 ranges from 30% to 50%. 5) The porosity ε2 in the first central region 104 ranges from 20% to 25%. 6) The porosity ε3 of the second region 105 is in the range of 35%≤ε3≤45%.

[0059] In this embodiment, ε3 / ε2 ≤ ε1 / ε2 is set, and the porosity of the current collector 106 side is set to be greater than that of the separator side. The current collector 106 side serves as the inlet for electrolyte injection and transport. The high porosity reduces capillary resistance, accelerates electrolyte penetration into the electrode, shortens formation time, and improves wetting uniformity. Maintaining a lower porosity on the separator side can suppress excessive accumulation of electrolyte at the separator-electrode interface, reduce side reactions caused by excessively high local concentrations, and improve interface stability. The above settings balance the contradiction between electrolyte transport, interface reaction, and mechanical stability, and are particularly suitable for high-load or high-rate battery systems.

[0060] 1.5≤ε1 / ε2≤3; optionally, 1.5≤ε1 / ε2≤2.5.

[0061] The aforementioned ratio range ensures that the current collector 106 side is sufficiently compacted to form a stable, low-resistance electron-conducting substrate, while preventing severe blockage of ion channels in the region due to excessive compaction, thereby achieving a forced quantitative balance between electron and ion conduction.

[0062] Specifically, the lower limit of this ratio range is 1.5. The porosity ε1 of the first region 103 must be at least 50% higher than the porosity ε2 of the first middle region 104. The current collector 106 side must be one of the regions with the highest porosity in the entire electrode thickness direction X, rather than simply being slightly higher than the intermediate layer, in order to actively construct a loose and porous interface layer for the current collector 106, thereby increasing the actual contact area between the active material and the current collector 106 and reducing the contact resistance. The upper limit of this ratio range is 3, which limits ε1 to a maximum of no more than three times ε2, thereby avoiding the low proportion of active material, loose coating and powder shedding, and reduction in volumetric energy density caused by excessively high porosity on the current collector 106 side.

[0063] Furthermore, narrowing the ratio range to the preferred range of 1.5 ≤ ε1 / ε2 ≤ 2.5 allows for the full realization of the aforementioned interface optimization benefits while also taking into account the mechanical strength of the coating and the feasibility of the coating process. This allows the coating to absorb and uniformly distribute the electron flow entering from the current collector 106 direction through its high porosity, while also utilizing its moderate mechanical strength to support the denser intermediate structure above. This prevents interface peeling due to rigidity differences during the volume expansion and contraction of the electrode during cyclic charging and discharging, thereby improving the battery's rate performance and peak power output. In addition, it provides clear guidance for formula design and rolling process parameter adjustment in the electrode manufacturing process, enabling engineers to precisely control the slurry solid content, coating thickness, and rolling line pressure based on this ratio range, resulting in good process operability and product consistency.

[0064] 1.5≤ε3 / ε2≤3; optionally, 1.4≤ε3 / ε2≤2.25; The aforementioned technical solution achieves a forced balance between enhancing the ion transport capability of the diaphragm side and preventing surface structural loosening and failure, while also synergizing with the aforementioned ratio on the current collector side (106). Within this range, the diaphragm side can function as a highly efficient ion current collector layer without being too porous and prone to powder shedding. This preferred ratio range is slightly narrower and lower than the ratio on the current collector side (106), reflecting a higher requirement for structural strength on the diaphragm side. While the electrode exhibits excellent rate performance, both structural integrity and capacity retention during long-term cycling are improved.

[0065] ε1 stores 30%~50% more electrolyte, reducing the interfacial resistance of electrons entering the current collector from the active material and promoting rapid lithium-ion exchange at the interface; ε2 stores 20%~25% to ensure the mechanical strength and volumetric energy density of the electrode, avoiding energy density loss due to excessive overall porosity; ε3 stores 35%~45% more electrolyte, reducing lithium-ion concentration polarization at the separator interface and accelerating lithium-ion migration from the electrode to the separator. Ultimately, this achieves a balance between high energy density, high rate capability, and long cycle life.

[0066] In some embodiments of this application, along the thickness direction X of the active material layer 107, with the side surface of the current collector 106 as Z=0, the side surface away from the current collector 106 as Z=H, and the center of the first central region 104 as Z=H / 2, the porosity ε(Z) at any thickness position Z satisfies the following functional relationship: ε(Z)=ε min +(ε max -ε min )×[(2Z / H-1) 2 ].

[0067] Among them, ε(0) ≤ε(H), ε(H / 2)= εmin , ε max The maximum porosity corresponding to the first region 103 and the second region 105, ε min The minimum porosity corresponds to the first central region 104.

[0068] A parabolic porosity distribution curve is used to create a continuous and smooth gradient transition between the current collector 106 side and the diaphragm side, achieving smooth ion transport in the thickness direction X of the active material layer 107. Specifically, this function has the center plane of the electrode Z=H / 2 as the axis of symmetry, where the porosity is at its minimum value ε. min The core layer serves as a mechanical support, effectively bearing the main volume expansion stress of the electrode and ensuring a high amount of active material per unit volume. Along the direction from the center to both sides, the porosity increases symmetrically with a square relationship, reaching its maximum values ​​at Z=0 and Z=H respectively. Since ε(0) ≤ ε(H), meaning the porosity on the current collector 106 side surface is lower than that on the separator side surface, it matches the actual transport requirements of lithium ions injected from the separator side. The porosity at any location along the entire electrode thickness is uniquely determined by this parabolic formula. During the transition from the central dense layer to both sides, the rate of change of porosity gradually increases from zero at the center, reaching its maximum near the surface. Therefore, the DC internal resistance of the electrode 102 is reduced, the rate performance is improved, and the capacity decay caused by interlayer interface stress mismatch during cycling is effectively suppressed.

[0069] like Figure 4 As shown, in some embodiments of this application, the electrode sheet 102 has a first edge 108 and a second edge 109 disposed opposite each other along its width direction Y. The active material layer 107 includes a third region 110, a second central region 111, and a fourth region 112 disposed sequentially along the width direction Y. The third region 110, the second central region 111, and the fourth region 112 are spatially overlapping regions formed by the first region 103, the second region 105, and the central region intersecting each other in the width direction Y of the electrode sheet. Among them, the second central region 111 is located between the third region 110 and the fourth region 112, and the porosity of the second central region 111 is greater than that of the third region 110, and the porosity of the second central region 111 is greater than that of the fourth region 112.

[0070] Optionally, the electrode sheet 102 includes a tab 101, which can be disposed with either the first edge 108 or the second edge 109. Specifically, the third region 110, the second middle region 111, and the fourth region 112 are spatially intersecting combinations of the first region 103 on the current collector side, the first middle region 104 on the middle side, and the second region 105 on the diaphragm side, each extending in the width direction Y. It can be understood that the setting of this width direction Y is a spatial superposition and control of the already constructed thickness direction X gradient, that is, the cross-sections at different width positions of the electrode sheet all maintain the aforementioned thickness direction X gradient characteristics, but the overall porosity levels of different cross-sections are different.

[0071] In the above embodiments, the spatially overlapping region refers to the fact that the third region 110, the second middle region 111, and the fourth region 112 are not entirely new structures independent of the thickness direction, but rather three-dimensional composite regions formed by the spatial coupling and intersection of the thickness direction gradient structure and the width direction gradient structure.

[0072] For example, the third region 110 is the spatial overlap of the first region 103 (current collector side) in the thickness direction X and the third region 110 (edge ​​side) in the width direction. This region has both the porosity characteristics of the current collector side and the porosity characteristics of the edge side in the width direction. For the third region 110, the porosity shows a trend of first decreasing and then increasing along the direction from the current collector 106 toward the membrane.

[0073] For example, the second central region 111 is the spatial overlap between the first central region (central part) in the thickness direction X and the second central region 111 (central side) in the width direction. Along the direction of the current collector 106 toward the membrane, the porosity of this region exhibits a trend of "first decreasing and then increasing." In the width direction, the second central region 111 corresponds to the central side of the electrode, where the porosity is at the peak of the width direction gradient and monotonically decreases towards both edges. When the two are coupled within the second central region 111, the "U-shaped" gradient in the thickness direction dominates the porosity change along the thickness direction, while the high porosity characteristic of the center in the width direction is superimposed on it as a substrate, ultimately forming a non-monotonic distribution of "first decreasing and then increasing." This distribution allows the second central region 111 to retain the energy storage framework function of the low porosity in the central part in the thickness direction, while compensating for the ion transport requirements of the central region through the high porosity of the central side in the width direction, thus avoiding the ion transport bottleneck caused by the superposition of double low porosity in the central region. For example, the fourth region 112 is the spatial overlap between the second region 105 (diaphragm side) in the thickness direction X and the fourth region 112 (the other edge) in the width direction Y. Along the direction of the current collector 106 toward the diaphragm, the porosity of this region exhibits a trend of first decreasing and then increasing. In the width direction Y, the fourth region 112 corresponds to the other edge of the electrode, where the porosity is at the trough of the width direction Y gradient and monotonically increases towards the center. When both are superimposed within the fourth region 112, the increasing gradient in the thickness direction X interacts with the low porosity characteristic of the edge in the width direction Y, causing the porosity change along the thickness direction X to be modulated by the edge effect in the width direction Y, ultimately forming a distribution that first decreases and then increases. This distribution allows the fourth region 112 to retain the ion channel function of high porosity on the diaphragm side in the thickness direction, while also enhancing the structural stability of the edge through low porosity on the edge side in the width direction, avoiding the decrease in mechanical strength and the risk of powder shedding caused by the superposition of double high porosity in the edge region.

[0074] It is understandable that the trend of the three overlapping regions first decreasing and then increasing along the thickness direction is not a new feature independent of the gradients in the thickness direction X and the width direction Y, but rather the result of the spatial coupling of the gradients in the two dimensions. This trend is the result of the combined effect of the high gradients on both sides and the low gradient in the middle of the thickness direction X, and the high gradient in the center and the low gradient at the edge of the width direction Y.

[0075] For example, if the porosity of the central region in the electrode width direction Y is 5 to 10 percentage points higher than that of the edge region, the central region can maintain the lithium-ion concentration balance with a more abundant ion supply capacity during high-rate charging, significantly delaying the arrival time of the lithium plating potential. In addition, after the width direction Y gradient is combined with the aforementioned thickness direction X gradient, the active material layer 107 forms a three-dimensional pore network in three-dimensional space with an overall high porosity in the central region, an overall low porosity in the edge region, and the thickness direction X in each width position maintaining "moderate on the current collector 106 side - dense in the middle - highest on the separator side". This allows the cell to obtain a pore structure that adapts to its respective thermodynamic and kinetic conditions from the edge to the center in the planar direction. The final effect is a significant reduction in the overall lithium plating risk of the cell, an extension of cycle life, and a systematic improvement in the uniformity of electrochemical reactions in the electrode width direction Y.

[0076] The middle circle refers to the central circular area defined by the geometric center of each electrode layer in the plane formed by its width and length directions, with a radius of 10% to 30% of the shorter side dimension of the electrode. Preferably, the radius of the middle circle is 15% to 25% of the shorter side dimension of the electrode. This area is located at the thermal and current center of the battery cell, where heat dissipation conditions are worst and local current density is highest, making it the main location for the "middle circle black spot" failure phenomenon.

[0077] The above structure actively compensates for the problem of excessively rapid ion consumption in the middle area of ​​the battery cell due to poor heat dissipation and high local current density, while suppressing the low porosity disadvantage naturally formed in the edge area due to fast drying rate and concentrated rolling pressure, thus achieving comprehensive control of porosity distribution in three-dimensional space.

[0078] In some embodiments of this application, the porosity gradually increases along the direction from the third region 110 toward the second central region 111; and the porosity gradually decreases along the direction from the second central region 111 toward the fourth region 112.

[0079] The above-described structure, based on the porosity distribution in the width direction Y that is high in the middle and low at both ends, further defines the porosity as a monotonically continuous gradual change from the edge to the center. Specifically, the porosity gradually increases from the third region 110 (towards the first edge 108) towards the second middle region 111 (central region), enabling the central region of the electrode to obtain sufficient ion supply capacity to match the high current density and high heat accumulation conditions; the porosity gradually decreases from the second middle region 111 towards the fourth region 112 (towards the second edge 109), forming a complete edge-high-edge-low gradual waveform.

[0080] This continuous gradient design eliminates porosity jump interfaces, allowing for continuous variation in resistance as ions diffuse in the planar direction, thus reducing current abrupt changes caused by local concentration polarization. This width-direction Y-gradient orthogonally superimposes with the aforementioned thickness-direction X parabolic gradient, enabling the active material layer 107 to form a three-dimensional porous network with a smooth transition from the current collector 106 to the separator, and from the edge to the center. This eliminates both impedance jumps in the thickness-direction X and performance precipitates in the width-direction Y, resulting in a reduction in the overall lithium plating risk of the secondary battery 1 and an extension of its cycle life. In particular, it systematically improves the electrochemical reaction uniformity in the width-direction Y of the electrode sheet 102.

[0081] In some embodiments of this application, the width of the electrode sheet 102 is W; the second central region 111 is a region extending 0.1W from the center line of the electrode sheet to both sides, and the third region 110 and the fourth region 112 are regions extending 0.4W from the edges of the electrode sheet towards the center. The porosity of the third region 110 is ε4, the porosity of the fourth region 112 is ε5, and the porosity of the second central region 111 is ε6. ε4, ε5, and ε6 satisfy at least one of the following: 1) 1.5 ≤ ε6 / ε4 ≤ 3; 2) 1.5≤ε6 / ε5≤3; 3) The porosity ε4 in the third region 110 ranges from 15% to 25%. 4) The porosity ε5 in the fourth region 112 ranges from 15% to 25%. 5) The porosity ε6 of the second central region 111 ranges from 35% to 50%.

[0082] The setting of 1.5≤ε6 / ε4≤3 limits the spatial range and porosity ratio of the high-porosity region at the center (0.1W on each side of the center) and the low-porosity region at the edge (0.4W on each side) along the width direction Y. This ensures that the geometric scale of the porosity gradient corresponds to the actual thermo-electrochemical distribution characteristics of the cell. The porosity of the central region is set to be higher than that of the edge region to match the higher current density and heat generation conditions in the central region. The lower limit of the ratio of 1.5 ensures that there is a sufficient porosity difference between the center and the edge to form ion concentration-driven diffusion along the width direction Y, alleviating lithium-ion depletion in the central region. The upper limit of the ratio of 3 prevents the porosity difference between the center and the edge from being too large, reducing the risk of warping or cracking in the width direction Y due to different shrinkage rates. When the geometric quantization partitioning in the width direction Y is combined with the porosity parameter in the thickness direction X, the pore structure of the electrode in three-dimensional space corresponds to the functional requirements of each position, which helps to suppress the black spot phenomenon in the middle circle, while the side reactions and lithium plating risk in the edge region can also be controlled to a certain extent.

[0083] The formula 1.5 ≤ ε6 / ε5 ≤ 3 sets a quantitative range of 1.5 to 3 for the porosity ratio between the second central region 111 and the fourth region 112 (on the side of the second edge 109). This ensures that the porosity of the two edges in the width direction Y of the electrode is reduced to the same proportional level as the central region. The lower limit of this ratio, 1.5, ensures that there is a sufficient porosity difference between the center and the second edge 109 to maintain the ion concentration-driven diffusion capability along the width direction Y, avoiding insufficient ion supply to the central region due to high porosity on one side. The upper limit of the ratio, 3, prevents excessive porosity difference between the center and the second edge 109, helping to reduce the risk of electrode warping or coating peeling caused by uneven mechanical properties in the width direction Y, and avoiding difficulties in controlling coating uniformity due to excessive deviation of the porosity setting values ​​on both sides. This numerical relationship is independent of the aforementioned ε6 / ε4 ratio range, allowing the specific values ​​of ε4 and ε5 to be independently adjusted on both sides of the electrode width direction Y according to actual process deviations or different cell packaging methods. At the same time, it keeps the porosity difference between the central region and the two sides within a reasonable ratio range, providing a more flexible control method for the engineering implementation of the width direction Y gradient design.

[0084] The porosity ε4 of the third region 110 ranges from 15% to 25%, setting an absolute value range of 15% to 25% for the porosity of the low-porosity region at the Y-edge in the width direction. This limits the porosity of the third region 110 (towards the first edge 108) to a relatively low level. The lower limit of 15% ensures that the edge region has sufficient channel space to maintain basic ion conductivity and electrolyte wetting ability, preventing the active material in this region from being unable to participate in electrochemical reactions due to excessively low porosity, thus reducing the effective utilization area of ​​the electrode. The upper limit of 25% prevents the edge region from having excessively high porosity, which would weaken the suppression effect on side reactions and lithium plating risks. It also prevents the porosity difference between the edge region and the central high-porosity region from being too small, resulting in insufficient driving force for Y-ion concentration-driven diffusion in the width direction. By controlling ε4 within the range of 15% to 25%, this low-porosity edge layer can form a sufficient performance difference with the central region with a lower porosity state. At the same time, when combined with the typical value of ε6 (central region) of about 40%, ε6 / ε4 can naturally fall within the ratio range of 1.5 to 3, making the numerical constraints of the width direction Y gradient design both engineering-friendly and feasible.

[0085] The porosity ε5 of the fourth region 112 ranges from 15% to 25%, setting the same absolute value range of 15% to 25% for the low-porosity region on the other side of the width direction Y as the third region 110. This limits the porosity of the fourth region 112 (on the side of the second edge 109) to a similarly low level as the third region 110. The lower limit of 15% ensures that this side edge has basic ion conduction and electrolyte wetting capabilities, preventing the active material from failing to participate effectively in electrochemical reactions due to excessively low porosity. The upper limit of 25% prevents the porosity of this side edge from being too high, weakening the suppression effect on edge side reactions and the risk of lithium plating, and ensuring a sufficient porosity difference between this region and the central high-porosity region to maintain ion concentration-driven diffusion in the width direction Y. By controlling ε5 within the range of 15% to 25%, consistent with the range of ε4, the porosity of the two edges on both sides of the electrode width direction Y can be independently selected within this common range. This provides a flexible process window for differentiating the porosity of the two edges due to the characteristics of the coating equipment or the different winding directions of the battery cell in actual production. At the same time, the porosity of both edges is lower than that of the high-hole area ε6 in the center, thus forming a symmetrical or asymmetrical gradient distribution pattern of low holes on both sides and high holes in the center in the width direction Y.

[0086] The porosity ε6 of the second central region 111 ranges from 35% to 50%, setting an absolute value range of 35% to 50% for the porosity of the central high-porosity region. This ensures that the porosity of the second central region 111 (the central region in the width direction Y) is maintained at a high level. The lower limit of 35% ensures that the central region has sufficient channel space to accommodate enough electrolyte and maintain high ion conductivity, thereby matching the high current density and heat generation conditions of the central region. The upper limit of 50% prevents the central region from having too high a porosity, which would lead to a low proportion of active material and a decrease in volumetric energy density. It also avoids structural loosening due to an overly porous coating during subsequent processing or cyclic expansion. By controlling ε6 within the range of 35% to 50%, and coordinating it with the low-porosity regions ε4 and ε5 at the edges (both 15% to 25%), the porosity ratios ε6 / ε4 and ε6 / ε5 between the center and the edge can naturally fall within the range of 1.5 to 3. This ensures that the numerical constraints of the width-direction Y-gradient design are consistent with engineering requirements. At the same time, the high-porosity layer at the center provides sufficient ion supply to the central region of the cell with a high porosity state, which helps to alleviate the lithium-ion consumption exacerbated by heat accumulation and current concentration in this region.

[0087] In some embodiments of this application, along the width direction Y of the electrode, from the central region toward the third region 110 or the fourth region 112, the porosity decreases monotonically, and the decrease is linear or exponential.

[0088] The above structure further defines the decrease in porosity in the width direction Y from the center to both sides as either linear or exponential, giving the transition between the high-porosity zone in the center and the low-porosity zone at the edges a clear mathematical form.

[0089] When the porosity decreases linearly, it decreases uniformly along the width direction Y at a constant rate of change, forming a smooth transition with equal gradient between the center and the edge. This helps to maintain a uniform change in ion diffusion resistance along the width direction Y, while simplifying the zonal control strategy for coating die opening or drying temperature.

[0090] As the exponent decreases, the porosity decreases slowly from the center outwards, accelerates near the edge, or decreases rapidly and then levels off. This can be flexibly selected based on the actual thermo-electrochemical distribution characteristics of the battery cell, so that the ion buffering effect of the high-porosity zone in the center can be maintained over a wide range, while the suppression effect of the low-porosity zone at the edge can be quickly established in the local area.

[0091] Neither of these two decreasing methods involves abrupt changes or fluctuations in porosity. There is no interface for abrupt changes in pore structure at any position in the width direction Y. This helps to avoid excessive differences in local electrochemical performance caused by uneven porosity distribution. At the same time, it provides an operable process path for intermittent adjustment of slits or zoned control of drying air volume during the coating process.

[0092] In some embodiments of this application, the porosity at any point inside the active material layer 107 is determined by the coupled gradient distributions in the thickness direction X and the width direction Y. Specifically, the porosity distribution in the thickness direction X exhibits a bimodal function characteristic, while the porosity distribution in the width direction Y exhibits a function characteristic that monotonically decreases from the center towards both edges.

[0093] The above technical solution clarifies that the porosity of any point inside the active material layer 107 is determined by the gradient distribution coupling of the thickness direction X and the width direction Y, so that the pore structure of the electrode sheet 102 in three-dimensional space can obtain a complete mathematical description framework.

[0094] The porosity distribution in the thickness direction X exhibits a bimodal function characteristic, with a porosity peak on the current collector 106 side and a porosity valley on the separator side, and a porosity valley in the middle region. This gives the regions near the two surfaces in the thickness direction X of the electrode a high ion exchange capacity, which is adapted to the bidirectional transport requirements of lithium ions entering from the current collector 106 side and being injected from the separator side, respectively. The middle dense layer serves as the core framework for mechanical support and electronic conduction.

[0095] The porosity distribution in the width direction Y exhibits a function characteristic that monotonically decreases from the center to both sides of the edge, which maintains a high porosity level in the central region of the electrode to match the high current density and heat generation conditions there, while the porosity in the edge region is lower to suppress side reactions and the risk of lithium plating.

[0096] After the gradient distributions in two directions are coupled and superimposed within the same volume element, each position in the active material layer 107 obtains a unique porosity value determined by both the thickness and width coordinates. This allows the pore structure of the electrode between the current collector 106 side and the separator side, and between the center and the edge, to be configured differently according to their respective spatial positions and functional requirements. Compared to the scheme that only controls the porosity in a single direction, this three-dimensional coupling method can more comprehensively match the differences in thermo-electrochemical characteristics at different spatial positions during the actual operation of the battery cell.

[0097] For example, mercury intrusion porosimetry can be used to test the porosity of the active material layer. Specifically, the principle of mercury intrusion porosimetry is to utilize the non-wetting property of mercury in porous media, and to inject mercury into the pores of the coating under external pressure for testing. The smaller the pore size, the greater the pressure required. The amount of mercury injected under different pressures is recorded, and the pore size distribution and porosity are calculated using the Washburn equation.

[0098] The testing equipment can be a fully automated mercury porosimeter (pressure range from 0.5 psi to 60,000 psi, measurable pore size range from approximately 3 nm to 360 μm).

[0099] The specific test steps include: 1) Remove the current collector, take a pure coating sample, weighing 0.1~0.5g, and put it into the dilatometer; 2) Low-pressure analysis (<25psi) fills the large pores, followed by high-pressure analysis to gradually fill the micropores; 3) Record the pressure versus mercury inlet volume curve, and the software will automatically calculate the porosity and pore size distribution.

[0100] This application provides a secondary battery 1, which includes the electrode plate 102 in the above embodiments. This application provides an electrical device, which includes the secondary battery 1 in the above embodiments. Since both the secondary battery 1 and the electrical device include the aforementioned electrode plate 102, they also possess the aforementioned technical effects.

[0101] Although this application has been described with reference to preferred embodiments, various modifications can be made thereto and components can be replaced with equivalents without departing from the scope of this application. In particular, the technical features mentioned in the various embodiments can be combined in any manner, provided there is no structural conflict. This application is not limited to the specific embodiments disclosed herein, but includes all technical solutions falling within the scope of the claims.

Claims

1. An electrode sheet, characterized in that, include: current collector; An active material layer is disposed on the surface of at least one side of the current collector. The active material layer includes a first region, a first central region, and a second region sequentially disposed along the thickness direction. The thickness of the active material layer is H. The first region is a region extending from the surface of the current collector in a direction away from the current collector with a thickness range of 0.1H. The second region is a region of the active material layer extending from the surface of the current collector in a direction away from the surface of the current collector with a thickness range of 0.1H. The first central region is a region located in the thickness direction within a range of 0.4H to 0.6H from the surface of the current collector. Along the direction from the first region toward the first central region, the porosity of the active material layer shows a decreasing trend; along the direction from the first central region toward the second region, the porosity of the active material layer shows an increasing trend, and the amount of the increasing change is less than or equal to the amount of the decreasing change.

2. The electrode sheet according to claim 1, characterized in that, Along the direction from the first region toward the first central region, the porosity of the active material layer decreases monotonically, and the rate of decrease gradually decreases; along the direction from the first central region toward the second region, the porosity of the active material layer increases monotonically, and the rate of increase gradually increases.

3. The electrode sheet according to claim 1 or 2, characterized in that, The porosity of the first region is ε1, the porosity of the first middle region is ε2, and the porosity of the second region is ε3. ε1, ε2, and ε3 satisfy at least one of the following: 1) ε3 / ε2≤ε1 / ε2; 2) 1.5 ≤ ε1 / ε2 ≤ 3; optionally, 1.5 ≤ ε1 / ε2 ≤ 2.5; 3) 1.5 ≤ ε3 / ε2 ≤ 3; optionally, 1.4 ≤ ε3 / ε2 ≤ 2.25; 4) The porosity ε1 of the first region ranges from 30% to 50%. 5) The porosity ε2 in the first central region ranges from 20% to 25%. 6) The porosity ε3 of the second region is in the range of 35%≤ε3≤45%.

4. The electrode sheet according to claim 3, characterized in that, In the thickness direction of the active material layer, with the surface of the current collector side as Z=0, the surface facing away from the current collector as Z=H, and the center of the first central region as Z=H / 2, the porosity ε(Z) at any thickness position Z satisfies the following functional relationship: e(Z)=e min +(e max -e min )×[(2Z / H-1) 2 ] Among them, ε(0)≤ε(H), ε(H / 2)=ε min The ε max Corresponding to the maximum porosity in the first region and the second region, the ε min This corresponds to the minimum porosity in the first central region.

5. The electrode sheet according to any one of claims 1-4, characterized in that, The electrode sheet has a first edge and a second edge that are arranged opposite to each other along its width direction, and the active material layer includes a third region, a second middle region and a fourth region arranged sequentially along the width direction; The second central region is located between the third region and the fourth region, and the porosity of the second central region is greater than that of the third region and the porosity of the fourth region is greater than that of the third region.

6. The electrode sheet according to claim 5, characterized in that, The porosity gradually increases along the direction from the third region toward the second central region; the porosity gradually decreases along the direction from the second central region toward the fourth region.

7. The electrode sheet according to claim 5, characterized in that, The width of the electrode sheet is W; the second central region is a region extending 0.1W from the center line of the electrode sheet to both sides, and the third and fourth regions are regions extending 0.4W from the edges of the electrode sheet towards the center. The porosity of the third region is ε4, the porosity of the fourth region is ε5, and the porosity of the second central region is ε6, wherein ε4, ε5, and ε6 satisfy at least one of the following: 1) 1.5 ≤ ε6 / ε4 ≤ 3; 2) 1.5≤ε6 / ε5≤3; 3) The porosity ε4 of the third region ranges from 15% to 25%. 4) The porosity of the fourth region ε5 ranges from 15% to 25%. 5) The porosity of ε6 in the second central region ranges from 35% to 50%.

8. The electrode sheet according to any one of claims 5-7, characterized in that, Along the width direction of the electrode, from the central region to the third or fourth region, the porosity decreases monotonically, and the decrease is either linear or exponential.

9. The electrode sheet according to claim 8, characterized in that, The porosity at any point inside the active material layer is determined by the coupled gradient distribution in the thickness direction and the width direction; The porosity distribution in the thickness direction exhibits a bimodal function characteristic, while the porosity distribution in the width direction exhibits a function characteristic that monotonically decreases from the center to both sides of the edge.

10. A secondary battery, characterized in that, Includes the electrode sheet as described in any one of claims 1-9.

11. An electrical appliance, characterized in that, Includes the secondary battery according to claim 10.